Effect of side chain-backbone electrostatic interactions on the stability of alpha-helices. - Scheraga, H A (1985)
An apparent discrepancy between the observed stability of the C-peptide alpha-helix of ribonuclease A and that computed from the Zimm-Bragg parameters sigma and s (obtained by the host-guest technique) is resolved. Side chain-backbone ion-dipole interactions play a role in both systems. However, they are averaged out in the random copolymers used to determine sigma and s for charged residues such as glutamic acid but not in the specific-sequence copolymer, namely, the C-peptide, where they contribute significantly to the helix stability. In considering a specific-sequence alpha-helix, its intrinsic stabilizing free energy (expressed in terms of sigma and s) must be augmented by position-dependent stabilizing long-range electrostatic interactions.